Biofuel as an alternative for Sub-Saharan Africa’s transition to cleaner energy - Stephen Enyinnaya Eluwa; Oluwaseun Kilanko (Academia Green Energy)
Energy plays a vital role in the social and economic development of any nation. Compared to other regions of the world, Sub-Saharan Africa lags behind in energy access. About half of the population lacks access to electricity and other cleaner fuels. With vast arable land and good climatic and soil conditions, Sub-Saharan Africa could address its energy supply challenges through bioenergy. This article reviews the biofuel potential of some Sub-Saharan African countries, the reasons why biofuel is suitable for the region, and the barriers hindering its expansion and development. Findings from the review indicate that some progress has been made in bioethanol and biogas production; however, biodiesel production is still in its infancy stage in the region. Most of the feedstocks for biofuel production are from agricultural waste. Among the countries in Sub-Saharan Africa, South Africa and Kenya have shown great prospects in the development and utilization of biomass resources for the production of cleaner fuels. Biofuel adoption in the energy mix of Sub-Saharan African countries will reduce overdependence on the importation of crude oil, thereby saving huge foreign exchange. It will also provide employment to millions of people in the agricultural value chain through the cultivation of bioenergy crops. In terms of climate change mitigation, biofuel holds great potential in reducing carbon emission associated with fossil fuels.